PUPILS’ TRUST IN TEACHERS AS A KEY PREREQUISITE FOR CHILD SAFETY IN SCHOOL - Petrochko, Zhanna; Kyrychenko, Valentyna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article deals with the actual issue of safety of a child aged 11-15 years. Its purpose is to define and describe key prerequisite for a child's safety at school (5th-9th grade), based on an analysis of the essence of the safety and results of empirical studies. The novelty of the article is due to the necessity to immediately search for prerequisites, factors, tools and other factors to counteract and overcome bullying in the educational environment.The article reveals the essence of child safety, as well as indicators that can be used to monitor 5th-9th grade pupils’ safety at school are outlined. Based on survey of teenagers and teachers, as well as correlated relationships, it has been determined that trust in teachers is a prerequisite for a child's safety in the educational environment and manifestation of social behaviour by pupils. Conclusions concerning instruments of establishing trust between pupils and teachers at school and ensuring their safety are formulated.